Keindahan Bahasa Al-Quran : Analisis Makna Tersembunyi Dalam Kinayah - Arrasyid, Harun (Maliki Interdisciplinary Journal, 2025)
Kinayah is a form of figurative language in Arabic used to convey meaning indirectly through metaphorical or ironic expressions. Unlike majaz, which explicitly rejects the literal meaning due to contextual clues (qarinah), kinayah still allows the literal meaning to be understood, although the implied meaning is more dominant. In this case, the original meaning in kinayah serves as a bridge to a deeper understanding. Scholars of balaghah, such as al-Zarkasyi, explain that kinayah is an expression that does not directly mention the object or meaning, but rather hints at the actual meaning through other words. In the Qur’an, the use of kinayah not only beautifies the wording but also conveys profound divine messages filled with wisdom. Al-Zarkasyi mentions ten main purposes behind the use of kinayah, including demonstrating the greatness of Allah, maintaining linguistic politeness, conveying inner meanings, and delivering subtle but effective satire. This study analyzes five Qur’anic verses containing elements of kinayah, namely QS. Al-Baqarah [2]: 187 and 223, QS. Al-An’am [6]: 125, QS. Ali-‘Imran [3]: 90, and QS. Al-Mu’minun [23]: 27. Expressions such as bāshirūhunna and ḥarṡun are used to discuss marital relations politely. The phrase yasrah ṣadrahu depicts the openness of heart in accepting the truth of Islam. Meanwhile, lan tuqbal taubatuhum indicates a state of persistent disbelief until death, and fāra at-tannūr symbolizes the arrival of a great punishment. Through this approach, kinayah is understood not only as a literary style but also as an important tool for grasping the moral, social, and spiritual messages of the Qur’an in a deeper and more contextual manner